Conference Report: Christian Empowerment, Secularity and Church Development - Herbst, Michael; Todjeras, Patrick (Ecclesial Futures, 2025)
The article reports on the conference of the International Consulation for Ecclesial Futures, which took place in Halle in 2024, and summarizes the key discussion points and insights from the participants. The focus in Halle was on the topic of "empowerment", which was repeatedly confronted with the specific church situation in the highly secularized church context in East Germany. In addition to the theoretical study of the topic, field trips were of particular importance.